Phosphorylation-dependent regulation of the F-BAR protein Hof1 during cytokinesis - Meitinger, Franz; Hofmann, Astrid; Pereira, Gislene (Genes & development, 2011)
Spatial and timely coordination of cytokinesis is crucial for the maintenance of organelle inheritance and genome integrity. The mitotic exit network (MEN) pathway controls both the timely initiation of mitotic exit and cytokinesis in budding yeast. Here we identified the conserved F-BAR protein Hof1 as a substrate of the MEN kinase complex Dbf2-Mob1 during cytokinesis. We show that polo-like kinase Cdc5 first phosphorylates Hof1 to allow subsequent phosphorylation by Dbf2-Mob1. This releases Hof1 from the septin ring and facilitates Hof1 binding to the medial actomyosin ring (AMR), where Hof1 promotes AMR contraction and membrane ingression. Domain structure analysis established that the central, unstructured, region of Hof1, named the ring localization sequence (RLS), is sufficient to mediate Hof1's binding to the medial ring in a cell cycle-dependent manner. Genetic and functional data support a model in which Dbf2-Mob1 regulates Hof1 by inducing domain rearrangements, leading to the exposure of the Hof1 RLS domain during telophase.